1999
DOI: 10.1073/pnas.96.21.11866
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1-associated growth arrest is RB-dependent

Abstract: BRCA1 is a susceptibility gene for breast and ovarian cancer with growth-inhibitory activity for which the mechanism of action remains unclear. When introduced into cells, BRCA1 inhibits growth of some but not all cell lines. In an attempt to uncover the mechanism of growth suppression by BRCA1, we examined a panel of cell lines for their ability to reduce colony outgrowth in response to BRCA1 overexpression. Of all variables tested, only those cells with wild-type pRb were sensitive to BRCA1-induced growth su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
137
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 20 publications
15
137
0
2
Order By: Relevance
“…BRCA1 causes transcriptional activation of the p21 WAF1/Cip1 and Gadd45 genes (Somasundaram et al, 1997;Harkin et al, 1999;Jin et al, 2000a), which contibute to proliferation inhibition and cell cycle blockade. Several studies, including our own, document a direct interaction between the BRCA1 and RB1 proteins, through two sites within BRCA1: (1) the carboxylterminal TAD (Yarden and Brody, 1998); and (2) an amino-terminal site within aa 300-400 (Aprelikova et al, 1999;Fan et al, 2001c). Brca1 blocked entry into S-phase in Rb1 þ/þ cells but not in Rb1 À/À cells mouse embryo fibroblasts (MEFs), suggesting a requirement for Rb (Aprelikova et al, 1999).…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 73%
See 2 more Smart Citations
“…BRCA1 causes transcriptional activation of the p21 WAF1/Cip1 and Gadd45 genes (Somasundaram et al, 1997;Harkin et al, 1999;Jin et al, 2000a), which contibute to proliferation inhibition and cell cycle blockade. Several studies, including our own, document a direct interaction between the BRCA1 and RB1 proteins, through two sites within BRCA1: (1) the carboxylterminal TAD (Yarden and Brody, 1998); and (2) an amino-terminal site within aa 300-400 (Aprelikova et al, 1999;Fan et al, 2001c). Brca1 blocked entry into S-phase in Rb1 þ/þ cells but not in Rb1 À/À cells mouse embryo fibroblasts (MEFs), suggesting a requirement for Rb (Aprelikova et al, 1999).…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 73%
“…Various classes of proteins interact with BRCA1, including: (1) components of the basal transcription machinery [e.g., RNA helicase A and RNA pol II (Anderson et al, 1998;Schlegel et al, 2000a)]; (2) generalized transcriptional coactivators [p300, CBP, Brg1 (Bochar et al, 2000;Pao et al, 2000)] and corepressors [e.g., RbAp46, RbAp48, histone deacetylases-1,2, and CtIP (Yarden and Brody, 1998;Yu et al, 1998)]; (3) tumor suppressors [e.g., p53, RB1, BRCA2 (Chen et al, 1998;Ouichi et al, 1998;Yarden and Brody, 1998;Zhang et al, 1998;Aprelikova et al, 1999;Chai et al, 1999;Fan et al, 2001c)]; (4) steroid hormone receptors, estrogen receptor-a, and androgen receptor (Yeh et al, 2000;Fan et al, 2001a); (5) DNA repair proteins [e.g., Rad51, Rad50, hMSH2 (Scully et al, 1997b;Zhong et al, 1999;Wang et al, 2001a)]; (6) other sequence-specific transcription factors [e.g., c-Myc, Oct-1, and NF-YA Fan et al, 2002b)]; and (7) cell cycle regulatory proteins [e.g., BARD1, E2F1, cyclins (Wu et al, 1996;Wang et al, 1997)]. These interactions are summarized in Figure 1; and the significance of these interactions is discussed in ''Functional Activities of BRCA1''.…”
Section: Brca1 Protein: Protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that BRCA1 mRNA is highly expressed in late G1 phase of the cell cycle, whereas conditions that lead to cell cycle exit down-regulate the BRCA1 mRNA (Gudas et al, 1995(Gudas et al, , 1996Jin et al, 1997). However, despite the cell cycle dependence of BRCA1 mRNA expression, BRCA1 protein level does not change during the cell cycle (Aprelikova et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The process is complicated by cellular senescence or apoptosis in many cells engineered to overexpress the BRCA1 cDNA from heterologous promoters (Aprelikova et al, 1999;Shao et al, 1996;Wilson et al, 1997;Zhang et al, 1998). Since mouse embryos de®cient in Brca1 die early in development, a straightforward assay of function is to analyse human BRCA1 gene replacement vectors for their ability to rescue Brca1-de®cient mouse embryos.…”
Section: Introductionmentioning
confidence: 99%